2020
DOI: 10.1136/jclinpath-2020-206840
|View full text |Cite
|
Sign up to set email alerts
|

Implementing NGS-basedBRCAtumour tissue testing in FFPE ovarian carcinoma specimens: hints from a real-life experience within the framework of expert recommendations

Abstract: AimsNext Generation Sequencing (NGS)-based BRCA tumour tissue testing poses several challenges. As a first step of its implementation within a regional health service network, an in-house validation study was compared with published recommendations.MethodsEpithelial ovarian cancer (EOC) formalin-fixed paraffin-embedded specimens stored in the archives of the eight regional pathology units were selected from a consecutive series of patients with known BRCA germline status. Two expert pathologists evaluated tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…We confirmed the feasibility of tumor BRCA testing in the routine clinical setting, with a very low failure rate (less than 1%) and a turnaround time consistent with clinical need (median TAT less than two weeks), strengthening our previous results [ 21 ] and in line with the recently reported experience of other Italian groups [ 19 , 23 , 29 ]. However, both the studies of Marchetti [ 23 ] and Turchiano [ 29 ] were based on a fresh-frozen tissue approach, which was a very promising strategy to overcome the degradation and chemical modification of DNA resulting from formalin fixation and paraffin embedding, but it required framework and facilities (i.e., biobanking) not always available in hospitals.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We confirmed the feasibility of tumor BRCA testing in the routine clinical setting, with a very low failure rate (less than 1%) and a turnaround time consistent with clinical need (median TAT less than two weeks), strengthening our previous results [ 21 ] and in line with the recently reported experience of other Italian groups [ 19 , 23 , 29 ]. However, both the studies of Marchetti [ 23 ] and Turchiano [ 29 ] were based on a fresh-frozen tissue approach, which was a very promising strategy to overcome the degradation and chemical modification of DNA resulting from formalin fixation and paraffin embedding, but it required framework and facilities (i.e., biobanking) not always available in hospitals.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, different scientific Societies, including the American Society of Clinical Oncology (ASCO), the National Cancer Comprehensive Network (NCCN), the Society of Gynecologic Oncology (SGO), the European Society of Medical Oncology (ESMO) and the AssociazioneItaliana di Oncologia Medica (AIOM) have recommended BRCA1/2 testing at the time of EOC diagnosis [ 11 , 12 , 13 , 14 ]. Guidelines for Next Generation Sequencing (NGS)-based BRCA test implementation have been proposed [ 15 , 16 , 17 , 18 ] and the feasibility of tumor BRCA assessment has been recently documented [ 19 , 20 , 21 , 22 , 23 ]. However, some critical issues still need to be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…The BRCA gene has been shown to be a good predictor of ovarian cancer prognosis. Claudia Marchetti et al (17) and Daniela Rivera et al (18) showed that the IMPLEMENTATION of NGS based BRCA tumor tissue detection in FFPE ovarian cancer specimens confirmed that BRCA gene could predict the prognosis of patients. Genetic testing can be developed for patients through collaboration between pathology and genetics.…”
Section: Discussionmentioning
confidence: 97%
“…Despite this uncertainty in the estimate proportion, germline BRCA1/2 PVs were detected in all histological subtypes of OC. Also, in seven studies that incorporated an extra round of pathological revision in their study design, germline BRCA1/2 PVs were identified in all histological subtypes [1,28,31,34,42,47,48].…”
Section: Proportion Of Germline Brca1/2 Pvs Per Histological Subtypementioning
confidence: 99%